Alcohol-related cerebellar degeneration: not all down to toxicity?. Issue 1 (December 2016) - Shanmugarajah, Priya; Hoggard, Nigel; Currie, Stuart; Aeschlimann, Daniel; Aeschlimann, Pascale; Gleeson, Dermot; Karajeh, Mohammed; Woodroofe, Nicola; Grünewald, Richard; Hadjivassiliou, Marios
Abstract Background Alcohol-related cerebellar degeneration is one of the commonest acquired forms of cerebellar ataxia. The exact pathogenic mechanisms by which alcohol leads to cerebellar damage remain unknown. Possible autoreactive immune mediated mechanisms have not been explored previously. In this study, we aim to investigate the potential role of alcohol-induced immune mediated cerebellar degeneration. Methods Patients with ataxia and a history of alcohol misuse were recruited from the Ataxia and Hepatology tertiary clinics at Sheffield Teaching Hospitals NHS Trust. We determined the pattern of cerebellar involvement both on clinical (SARA score) and imaging (MRI volumetry and MR spectroscopy) parameters. In addition, HLA genotyping, serological markers for gluten-related disorders and serological reactivity on rat cerebellar tissue using indirect immunohistochemistry were assessed. Results Thirty-eight patients were included in the study all of whom had ataxia. The gait (97 %), stance (89 %) and heel-shin slide (89 %) were the predominant SARA elements affected. MRI volumetric and spectroscopy techniques demonstrated significant structural, volumetric and functional deficits of the cerebellum with particular involvement of the cerebellar vermis. Circulating anti-gliadin antibodies were detected in 34 % patients vs. 12 % in healthy controls. Antibodies to transglutaminase 6 (TG6) were detected in 39 % of patients and 4 % of healthy control subjects. Using immunohistochemistry, Purkinje cell and/or granular layer reactivity was demonstrated in 71 % of patient sera. Conclusions Alcohol induced tissue injury to the CNS leading to cerebellar degeneration may also involve immune mediated mechanisms, including sensitisation to gluten.